Therapeutic effects of pentoxifylline in propionic acid‐induced autism symptoms in rat models: A behavioral, biochemical, and histopathological study - Erdoğan, Mümin Alper; Tunç, Kerem Can; Daştan, Ali İmran; Tomruk, Canberk; Uyanıkgil, Yiğit; Erbaş, Oytun (International journal of developmental neuroscience, 2024)
Objective The role of propionic acid (PPA) in eliciting behaviors analogous to autism in rat models is a documented phenomenon. This study examines the therapeutic implications of pentoxifylline—an agent traditionally used for peripheral vascular diseases—on these autism‐like behaviors by modulating brain proteins and reducing pro‐inflammatory cytokines like tumor necrosis factor‐α (TNF‐α) in a rat model. Methods This research involved 30 male Wistar albino rats, which were divided into three distinct groups: a baseline control set, a PPA‐treated cluster receiving a 250 mg/kg/day dose of PPA via intraperitoneal injection for a span of five days followed by saline orally, and a PPA group administered an oral dose of pentoxifylline at 300 mg/kg/day over 15 days. Subsequent to the treatment phase, euthanasia was carried out for the extraction of brain and blood samples, which were then analyzed for histopathological and biochemical markers. Results The pentoxifylline‐treated subjects demonstrated a significant mitigation in the manifestation of autistic‐like behaviors, as assessed through a triad of social interaction tests. A noteworthy decline in TNF‐α levels was observed, alongside a significant rise in the concentration of adenosine triphosphate and nerve growth factor in brain tissue (p < 0.05). Histopathological analysis underscored a reduction in oxidative stress and a significant preservation of neuronal cell types, specifically pyramidal neurons in the hippocampal CA1 and CA3 regions and Purkinje cells in the cerebellum (p < 0.001). Conclusion Pentoxifylline treatment has been found to effectively reduce the behavioral symptoms associated with autism, as well as biochemical and histopathological disruptions induced by PPA in rat models, highlighting its potential as a neurotherapeutic agent. This study investigates the therapeutic effects of pentoxifylline on autism‐like symptoms in rats induced by propionic acid (PPA). Pentoxifylline treatment improved social behaviors, reduced TNF‐α and IL‐17 levels, decreased oxidative stress, and increased ATP and NGF levels, highlighting its potential as a neurotherapeutic agent for ASD.